IMPLEMENTASI PEMOTONGAN DAN PENYETORAN PAJAK PENGHASILAN FINAL DARI HASIL PENJUALAN LELANG TANAH DAN/ATAU BANGUNAN (STUDI PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) BANJARMASIN - Tri Walinda; Maya Sari Dewi (Universitas Lambung Mangkurat, 2020)
Final Income Tax is a tax imposed at certain rates and tax bases on income received or earned during the current year. KPKNL Banjarmasin is one of the DJKN work units whose main task is to conduct auctions. The purpose of this study is to implement the withholding and deposit of Final Income Tax from the sale of land and/or building auctions at the Banjarmasin KPKNL. Based on the results of research conducted at the Banjarmasin KPKNL, the withholding and deposit of the final PPh carried out was in accordance with applicable regulations.